Evaluation of Drug Abuse Education Program for Students through a Partnership Between Police and Schools - Rendra Eka Kumala; Kaniati Amalia; Amrozi Khamidi (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This study aims to evaluate the drug abuse education program for students implemented through a partnership between the Police and schools in Karawang Regency, particularly through the Sie Dokkes Unit of the Karawang Police Department. The research employed a qualitative approach with a descriptive method. Data sources included school representatives (principals, guidance and counseling teachers, and students) as well as police personnel (Sie Dokkes and the Narcotics Unit). Data were collected through in-depth interviews, observations of educational activities, and document analysis. Data analysis techniques involved data condensation, data display, and conclusion drawing. The results showed that the drug abuse education program had been fairly effective in increasing students’ knowledge and awareness of the dangers of drug abuse. The main supporting factors were the strong commitment and coordination between schools and the police, as well as the contextual educational approach through counseling sessions and case simulations. However, several challenges were identified, including limited human resources and the lack of structured and regular program schedules. The study concludes that the partnership between the police and schools serves as an effective strategy for fostering a drug-free educational environment.